Experimental and coupling analysis of municipal solid waste (MSW) shear strength under multiple influencing parameters - Muhammad Muneer; Dequan Kong; Rong Wan; Xinyang Liu; Qingxiang Song; Masood ur Rahman (PLoS ONE, 2026)
The production of municipal solid waste (MSW) in China is growing rapidly, and landfill is the primary treatment method. The shear strength of MSW is crucial to the stability and safety of landfills. However, there is limiting research available on how different environmental and compositional factors interactively influence MSW shear strength since some existing studies typically examine these variables in isolation. Through integrated testing and statistical modeling this looks into how environmental factors (moisture content 30–230%, organic matter content 15–75%, temperature 10–65°C and degradation time 15–190days) work together to change the shear strength of MSW. One hundred MSW samples were prepared according to field waste composition from Xi’an and were subjected to direct shear tests over a 190-day degradation period. The test results show that cohesion ( c ) decreased over time, to a minimum value of 0.17 kPa at 190 days, while angle of internal friction ( φ ) increased to 42.39° at 190 days. Both c and φ showed an initial increase followed by a decrease with temperature changes. The effect of organic matter on c decline was negligible, though φ increased during the early stage of degradation. Higher moisture content (80–130%) and organic matter (45–60%) along with temperatures between 10–35°C resulted in high φ values. High c values were achieved with 130% moisture content 15–30% organic matter and temperatures between 10 and 35 °C. Under the controlled conditions of the study the Mohr–Coulomb equation was modified to incorporate degradation effects, and multiple linear regression together with automatic linear modeling (ALM) were used to predict c and φ , yielding R 2 values of 0.622 and 0.468 respectively, demonstrating the models’ predictive accuracy. In practical engineering, the study’s outcomes will help to understand the effect of different parameters on the shear strength of MSW which can lead to achieve the landfill slope stability and the use of MSW as backfill material in building foundations under the controlled conditions of the study.